Eskimo schleppen Netze heimwärts, bei Okak 1912 - Bohlmann, Ernst, 1864-1945. (2001)
Photograph of a group of Inuit near Okak dragging a load of nets homeward, 1912. Three Inuit are sitting on a rock while one man is hauling the nets. A small white dog is also visible on the left side of the photograph. Photograph of a group of Inuit near Okak dragging a load of nets homeward, 1912. Three Inuit are sitting on a rock while one man is hauling the nets. A small white dog is also visible on the left side of the photograph.